Beta-carotene Oxygenase 2 (BCO2) Regulates the Mitochondrial Dynamics in Mice (FS06-06-19). (13th June 2019) - Lin, Dingbo; Wu, Lei; Guo, Xin; Wong, Siau Yen; Lu, Peiran; Clarke, Stephen; Lucas, Edralin A; Smith, Brenda; Chowanadisai, Winyoo; Wang, Weiqun; Medeiros, Denis
Abstract: Objectives: Beta-carotene oxygenase 2 (BCO2) is a carotenoid metabolic enzyme located to the inner membrane of mitochondria. Decreased expression of and mutations in BCO2 are associated with obesity and metabolic disorders in humans and mice. We recently reported that depletion of BCO2 alters mitochondrial respiratory activity. Here, we further present that BCO2 is important for mitochondrial dynamics and respiratory supercomplex formation in mice. Methods: Six-week-old male and female 129S6 (wild type, WT) and BCO2 knockout (KO) mice fed a chow diet were used in the current study. Hypothalamic tissues were collected for mitochondrial morphology by transmission electron microscopy, mitochondrial proteomics, and mitochondrial respiratory supercomplex formation and respiratory activity assays. Key proteins in mitochondrial dynamics, including OPA1, Mfn2, DRP1, p62, ULK1 were assessed by Western blot. Cardiolipin was measured by ELISA. Results: The results showed that mitochondrial complex I subunit NDUFA11 was more abundant, assembly of complex I into the I-III-IV-containing supercomplexes was greatly enhanced, yet complex III homodimer was diminished in the hypothalamus of the BCO2 knockout mouse, compared to the wild type. Decreases in mitochondrial respiration activities, disruption of mitochondrial elongation (e.g., increased DRP1 and pS757-ULK1), suppression of mitochondrial biogenesis (e.g., decreased PPARgamma and PGC-1alpha), promotion of mitochondrial oxidative stress, and elevation of the cardiolipin level occurred in depletion of BCO2. Conclusions: BCO2 is critical for the hypothalamic mitochondrial homeostasis through regulation of respiratory supercomplex formation, mitochondrial dynamics, and consequent oxidative stress. Funding Sources: N/A.